(untitled) (Fiep Bulletin - online, 2016)
Introduction: Chronic pulmonary disease (COPD) is characterized by the destruction of tracheobronchial tree which leads to damage in pulmonar and peripheral muscles, where the physical training of these patients are generally focused on improvement in aerobic fitness which provides improvement in activities of daily living and decreased sensation of dyspnea. Objective: To analyze by spirometry respiratory function of patients hospitalized with chronic obstructive pulmonary disease before and after performing a protocol of aerobic exercise on respiratory and peripheral muscles. Methods: This is uncontrolled clinical trial, a sample composed of 6 hospitalized patients submitted to a protocol of physiotherapy rehabilitation being evaluated hemodynamic parameters (systolic and diastolic blood pressure, heart rate, respiratory rate, subjective Borg scale, distance/time on the cycle ergometer and saturation peripheral oxygen) and spirometric variables (FVC, forced vital capacity, peak expiratory flow - PEF, forced expiratory volume in one second- FEV1 and Tiffenau index with the FEV1/FVC ratio. Results: After the implementation of the protocol and tabulation of data, can demonstrate an improvement in hemodynamic and spirometricvalues??, but wasn’t found statistically significant changes. Conclusions:It,s therefore concluded that despite not achieving statistical significance protocol resulted in improved data on population.